2007
DOI: 10.1074/jbc.m702246200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of the Catalytic Reaction Mechanism of Novel 1,2-α-L-Fucosidase from Bifidobacterium bifidum

Abstract: 1,2-␣-L-Fucosidase (AfcA), which hydrolyzes the glycosidic linkage of Fuc␣1-2Gal via an inverting mechanism, was recently isolated from Bifidobacterium bifidum and classified as the first member of the novel glycoside hydrolase family 95. To better understand the molecular mechanism of this enzyme, we determined the x-ray crystal structures of the AfcA catalytic (Fuc) domain in unliganded and complexed forms with deoxyfuconojirimycin (inhibitor), 2-fucosyllactose (substrate), and L-fucose and lactose (products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
102
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(113 citation statements)
references
References 66 publications
10
102
0
1
Order By: Relevance
“…The B. bifidum PRL2010 genome encodes various glycosyl hydrolases putatively implicated in degradation of mucinderived oligosaccharides, including a predicted cell wall-anchored endo-α-N-acetylgalactosaminidase (BBPR_0264), an enzyme that has been shown previously to catalyze the hydrolysis of the O-glycosidic α-linkage between GalNAc and serine/threonine residues of various mucin-type glycoproteins (30)(31)(32). Moreover, the genome of B. bifidum PRL2010 encodes a putative 1,2-α-Lfucosidase (BBPR_0193), as well as a predicted 1,3/4-α-L-fucosidase (BBPR_1360), which releases various α-linked L-fucoses from the oligosaccharide core of the mucin structure (33)(34)(35). Both fucosidases contain a signal peptide, but only BBPR_0193 contains an LPXTG motif, suggesting that this enzyme is secreted and anchored to the cell wall, whereas the presumed fucosidase encoded by BBPR_1360 contains two transmembrane domains, indicating that it is bound to the cell membrane.…”
Section: Resultsmentioning
confidence: 99%
“…The B. bifidum PRL2010 genome encodes various glycosyl hydrolases putatively implicated in degradation of mucinderived oligosaccharides, including a predicted cell wall-anchored endo-α-N-acetylgalactosaminidase (BBPR_0264), an enzyme that has been shown previously to catalyze the hydrolysis of the O-glycosidic α-linkage between GalNAc and serine/threonine residues of various mucin-type glycoproteins (30)(31)(32). Moreover, the genome of B. bifidum PRL2010 encodes a putative 1,2-α-Lfucosidase (BBPR_0193), as well as a predicted 1,3/4-α-L-fucosidase (BBPR_1360), which releases various α-linked L-fucoses from the oligosaccharide core of the mucin structure (33)(34)(35). Both fucosidases contain a signal peptide, but only BBPR_0193 contains an LPXTG motif, suggesting that this enzyme is secreted and anchored to the cell wall, whereas the presumed fucosidase encoded by BBPR_1360 contains two transmembrane domains, indicating that it is bound to the cell membrane.…”
Section: Resultsmentioning
confidence: 99%
“…GH29 enzymes retain glycosidases, whereas GH95 enzymes are inverting glycosidases (27)(28)(29)(30)(31)(32). Enzymes in GH29 exist in all domains of life, whereas GH95 members have not been found in animals (15,26).…”
mentioning
confidence: 99%
“…Enzymes in GH29 exist in all domains of life, whereas GH95 members have not been found in animals (15,26). Crystal structural studies have shown that GH29 enzymes have a conserved catalytic active site formed at one end of a (␤/␣) 8 triosephosphate isomerase (TIM) barrel domain, whereas GH95 enzymes have their active site formed by an (␣/␣) 6 helical barrel domain (22,23,(27)(28)(29). Besides GH29 and GH95 enzymes, A. thaliana also expresses a novel lipase-like fucosidase named AtFXG1, which has not been classified in CAZy (33).…”
mentioning
confidence: 99%
“…The residue that acts as a general base, corresponding to Glu400 in A. awamori glucoamylase, is substituted for a phosphate ion in both GH65 and GH94 (11). 3C, 3D, and 3E show GH78 α-L-rhamnosidase (43), GH92 α-mannosidase (44), and GH95 1,2-α-L-fucosidase (45), all of which hydrolyze oligo-and polysaccharides consisting of monosaccharides other than glucose. These enzymes are composed of multiple domains in addition to the catalytic (α/α) 6 barrel, and thus form complicated structures.…”
Section: Enzymes Structurally Related To Enzymes Of the Families Gmentioning
confidence: 99%
“…GH95 1,2-α-L-fucosidase also adopts a unique reaction mechanism, in which an asparagine residue activated by a neighboring aspartic acid residue acts as a base (45,46). It is intriguing that the catalytic mechanisms of enzymes that hydrolyze oligo-and polysaccharides consisting of monosaccharides other than glucose are different from those of GH15, GH37, and GH63.…”
Section: Enzymes Structurally Related To Enzymes Of the Families Gmentioning
confidence: 99%